Hydrothermal synthesis of Fe3 O4-ZnO nanocomposites for removing fluoride from water - Salimeh Kimiagar; Hoda Mirazimi (Progress in Physics of Applied Materials)
Numerous nations are grappling with a significant challenge related to the prevalence of fluorosis, stemming from elevated fluoride levels in drinking water. This study aims to investigate avenues for eliminating fluoride from water solutions utilizing cost-effective, nontoxic, and readily available adsorbents. In this research, -ZnO nanocomposites were synthesized using the hydrothermal method which is a simple and environmentally friendly method that can be easily performed on a large scale. X-Ray diffraction analysis and Williamson-Hall plots were used to study the phase purity, crystallite size, strain, lattice constant, and d-spacing of the samples. The morphology of the samples was investigated through Scanning Electron Microscopy and Transmission Electron Microscope. The formation of nanocomposites was investigated by Vibrating Sample Magnetometer analyses. The -ZnO nanocomposites were then used for fluoride removal from water. The results showed that -ZnO-2 could absorb 78% of the fluoride after 80 minutes. Then, -ZnO-2 was collected using a magnet within 50 seconds. These results are important in that, despite their simplicity, it has no side effects on the environment.